2018
DOI: 10.1016/j.drugalcdep.2018.05.032
|View full text |Cite
|
Sign up to set email alerts
|

A novel mHealth application for improving HIV and Hepatitis C knowledge in individuals with opioid use disorder: A pilot study

Abstract: This HIV+Hepatitis Education intervention was associated with significant and sustained improvements in knowledge of HIV + HCV transmission and risk behaviors in this vulnerable group of individuals with OUD. Given the continuing opioid epidemic, efforts are urgently needed to reduce HIV and HCV contraction and transmission among individuals with OUD. Mobile health educational interventions may offer a time- and cost-effective approach for addressing these risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
2
9
1
1
Order By: Relevance
“…Also, some studies conducted in HICs and other LMICs indicated a limited level of research on the use of mHealth interventions for diagnostic purposes [ 50 , 51 ] which are consistent with our study findings. Furthermore, there is a higher level of research from some studies conducted in HICs and other LMICs which showed that health workers used tablets, smartphones, personal digital assistants, handheld devices, and mobile phones to support disease diagnosis and treatment procedures [ 39 42 , 44 , 45 , 47 , 49 51 ] which are not consistent with this study findings.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Also, some studies conducted in HICs and other LMICs indicated a limited level of research on the use of mHealth interventions for diagnostic purposes [ 50 , 51 ] which are consistent with our study findings. Furthermore, there is a higher level of research from some studies conducted in HICs and other LMICs which showed that health workers used tablets, smartphones, personal digital assistants, handheld devices, and mobile phones to support disease diagnosis and treatment procedures [ 39 42 , 44 , 45 , 47 , 49 51 ] which are not consistent with this study findings.…”
Section: Discussioncontrasting
confidence: 93%
“…Roesler et al and Ochalek et al conducted studies in Brazil and the US which showed a limited level of research on the use of mHealth to prevent transmission of diseases from one individual to another [ 48 , 49 ] which are similar to our findings. Also, some studies conducted in HICs and other LMICs indicated a limited level of research on the use of mHealth interventions for diagnostic purposes [ 50 , 51 ] which are consistent with our study findings.…”
Section: Discussionsupporting
confidence: 90%
“…Our review study are partly consistent with other studies carried out in high-income countries (HICs) (38)(39)(40)54) which found the use of mHealth to manage chronic disease conditions like HIV, TB, hypertension and cancer. Similar studies conducted in low-and middle-income countries (LMICs) also agree with the findings of this review study which revealed the use of mHealth improved medication (51,52) which are similar to our findings. In addition, some studies conducted in HICs and other LMICs indicated limited level of research on the use of mHealth interventions for diagnostic purposes (37,47) which are different from the study findings.…”
Section: Discussionsupporting
confidence: 93%
“…However, educational interventions may be often the only ones available (e.g., prevention of sexually transmitted disease) in some conditions and can reach a considerable impact when implemented consistently and repeatedly (Dryden‐Peterson et al., ). Thus, this requires the availability of consistent resources to deliver tailored and structured educational interventions that can have a positive impact on both individual and public health (Ochalek, Heil, Higgins, Badger, & Sigmon, ).…”
Section: Implications For Practice and Researchmentioning
confidence: 99%